Effect of Time Fermentation on The Microbiological Properties of Coconut Water Kefir - Raafi, Muhammad; Jameelah, Maryam; Tiara, Analekta (Universitas Al Azhar Indonesia, 2023)
Coconut water is one of the popular drinks in tropical countries, it has been used widely as an isotonic drink, nutrient-rich, and has other beneficial functions. Many advantages of coconut water also make this product explored by many researchers as a synbiotic or even probiotic drink. This research investigates the impact of time fermentation on the microbiological properties of coconut water kefir. The study employs various time intervals during the fermentation process to explore changes in mesophilic bacteria, lactic acid bacteria, and total yeast and mold. By analyzing the microbiota present at different fermentation times (6, 12, 18, 24, and 48 hours), this research aims to elucidate how time affects the number of beneficial potential probiotic strains, such as lactic acid bacteria and yeast. The findings of this study showed that 24 hours of fermentation time gave the highest number of lactic acid bacteria (7.23 Log CFU/mL), the highest number of mesophilic bacteria (7.52 Log CFU/mL), and total yeast and mold (7.14 Log CFU/mL). Additionally, the inhibitory effects of coconut water kefir on two different kinds of pathogenic bacteria were examined using well diffusion, even though there was no inhibition zone. In conclusion, 24 hours is the best fermentation time to produce coconut water kefir which showed the highest increase of lactic acid bacteria, mesophilic bacteria, and total yeast and mold.